Advokasi Politik Feminisme: Analisis Strategi Jakarta Feminist dalam Mempengaruhi Formulasi Kebijakan Gender - Nisaul Istiqomah; Ajeng Roro Syanti; Ika Arinia Indriyany (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the political advocacy strategies employed by Jakarta Feminists in influencing the policy formulation process related to gender equality issues in Indonesia through various forms of social mobilization, including digital campaigns, public education, and collaboration with other civil society organizations. Jakarta Feminists emerged as a feminist collective actively advocating against policies deemed discriminatory against women and vulnerable groups. This study used a qualitative approach with a literature study method by Bogdan and Taylor as cited by Lexy J. Moleong. Data were obtained through literature studies from scientific journals, news, and social media content analysis. The analysis was conducted using Sidney Tarrow's social movement theory, with indicators of Political Opportunity Structure, Mobilizing Structures, Framing Processes, and Repertoires of Contention. The results show that Jakarta Feminists utilize political momentum, public issues, and digital spaces as strategies to expand support and pressure policymakers. In addition, the use of social media, the production of public knowledge, and collaboration with civil society organizations are forms of mobilization that strengthen the movement's advocacy capacity. Jakarta Feminists also successfully frame issues so that they are easy to understand. Collective action is also Jakarta Feminist's most iconic form of action and a consistent form of public pressure on the government each year. This study concludes that Jakarta Feminist's advocacy strategy demonstrates how feminist-based social movements can leverage political opportunities and mobilization structures to influence the discourse and direction of gender policy in Indonesia.